Highly ordered carbon-based nanospheres with high stiffness. (August 2016) - Ozden, Sehmus; Tiwary, Chandra Sekhar; Yao, Jianyu; Brunetto, Gustavo; Bhowmick, Sanjit; Asif, Syed; Vajtai, Robert; Ajayan, Pulickel M.
Abstract: Understanding properties of individual nanostructures, such as mechanical properties and deformation mechanism, aid to control their properties for specific applications. Here we report, the mechanical properties of individual boron and nitrogen doped carbon-based nanospheres (CNS) using in-situ nano-compression testing in a scanning electron microscopy (SEM). The in-situ SEM characterizations showed classical sphere deformation during initial loading and it can be deformed till 40–50 percent. Elastic modulus of spheres is 33.3 GPa which has been determined using unloading curves. The mechanical properties of CNS structures are quite outstanding when it is compared to some other conventional nanomaterials such as polymer-based spheres and nanotube structures.